Effect of sun flower oil addition (Helianthus annuus) in diet on nutrient intake, growth performance and characteristics of estrous of pre-mating Garut sheep - L, Khotijah; R, Zulihar; MA, Setiadi; KG, Wiryawan; DA, Astuti (Indonesian Journal of Animal and Veterinary Sciences, 2014)
Nutritional status of ewes at pre-breeding phase is critical for good reproductive process. Thirty-two ewes Garut sheep (initial body weight 22.5Â±2.21 kg) were used in a completely randomized design to evaluate the effects of addition of sunflower oil in the diet on nutrient intake, growth performance and characteristics of estrous of pre-mating garut sheep. Ewes were fed grass and supplemented with one of four isonitrogenous high concentrate diets containing four levels of sunflower oil; they were (M0) no addition of sunflower oil; (M1) 2% sunflower oil; (M2) 4% sunflower oil and (M3) 6% sunflower oil addition. Results showed that the addition significantly reduced dry matter intake (p < 0.05), highly significantly reduce crude protein, Ca and P intake (p < 0.01), higly significant increased ether extract intake (p < 0.01) and significantly increased long of estrous (p < 0.05). There was no difference in crude fiber intake, TDN intake, body weight gain, length of estrous onset and response of estrous for ewes fed the four experimental diets. Response on estrous of treatments M0, M1, M2 and M3 were 62.50; 50.00; 75,00 and 62.5% respectively. It is concluded that the addition of sunflower oil up to 6% in the pre-mating ration affects the nutrient intake without interferering the performance, and it tends to improve the charachteristic estrous of Garut ewes. Key Words: Nutrient Intake , Estrous, Garut Sheep, Performance, Sunflower Oil